Recombinant streptavidin fusion proteins as signal reporters in rapid test of human hepatitis C virus infection. Issue 3 (23rd October 2018) - Zhou, Shengliang; Cao, Shinian; Ma, Guoliang; Ding, Tielin; Mu, Jingjing; Han, Weilu; Sun, Dongxu; Chen, Caifa
Abstract : Background: Early diagnosis of hepatitis C virus (HCV) infection is very important for the treatment of the disease. Development of sensitive and specific rapid detection assays is of great significance for the diagnosis. Here, we describe a promising method of using gold‐labeled streptavidin fusion proteins as novel signal reporter in a rapid detection assay for HCV infection. Methods: Recombinant genes encoding streptavidin fused with Escherichia coli maltose‐binding protein (MBP) or with a portion of bacterial translational initiation factor 2 were cloned in expression vectors pMAL‐5CX and pET28 and transformed in proper Escherichia coli host strains. The genes were induced and streptavidin fusion proteins, named M‐STV and IF‐STV, respectively, were purified by affinity chromatography to over 90% purity. The biotin‐binding activity of M‐STV and IF‐STV was tested by enzyme‐linked immunosorbent assay (ELISA). M‐STV was labeled with colloidal gold nanoparticles and used as a signal reporter to develop a lateral flow‐based rapid test for detecting anti‐HCV antibodies in human blood samples. Results: M‐STV showed slightly higher biotin‐binding activity and similar binding specificity as compared to commercial streptavidin. The gold‐labeled M‐STV bound specifically to biotin moieties immobilized on the rapid test strips in a dose‐responsive manner and was successfully used in detecting HCV antibodies in serum samples of patients infected with HCV. The rapid test displayed higher detection sensitivity than gold‐labeled commercial NeutrAvidin. Conclusion: Our results indicate that gold‐labeled M‐STV is a promising agent in rapid tests of HCV infection and possibly other viral infections.